2008
DOI: 10.1002/jca.20161
|View full text |Cite
|
Sign up to set email alerts
|

Refractory thyrotoxicosis induced by iodinated contrast agents treated with therapeutic plasma exchange. A case report

Abstract: Excess free iodide in the blood (ingested or injected) may cause thyrotoxicosis in patients at risk. Iodinated contrast solutions contain small amounts of free iodide and may be of significance for patients affected by Graves' disease, multinodular goiter or living in areas of iodine deficiency. Herein, we report a 57 elderly woman with a clinical history of multinodular goiter presented with a thyrotoxicosis induced by an iodinate contrast agent used during computed tomography scan. Because of the patient's r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…However, in patients with iatrogenic thyrotoxicosis or for whom antithyroid drugs are contraindicated or who are resistant to antithyroid drugs, further therapies are needed to restore euthyroid hormone status. The reported cases suggested that therapeutic plasma exchange (TPE) has been used as an additional treatment or preparation for surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with iatrogenic thyrotoxicosis or for whom antithyroid drugs are contraindicated or who are resistant to antithyroid drugs, further therapies are needed to restore euthyroid hormone status. The reported cases suggested that therapeutic plasma exchange (TPE) has been used as an additional treatment or preparation for surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The definitive therapeutic treatment for thyroid storm is to perform surgical thyroidectomy or radioactive iodine treatment to prevent recurrence of symptoms and the associated mortality. It is preferred that patients attain a euthyroid state prior to undergoing surgery . Data demonstrates that euthyroid patients have decreased thyroid vascularity and improved surgical planes and that thyrotoxic patients experience significant perioperative mortality due to precipitation of thyroid storm .…”
Section: Discussionmentioning
confidence: 99%
“…There are 13 cases of therapeutic plasma exchange (TPE) for thyroid storm or severe thyrotoxicosis in the literature. [8][9][10][11][12][13][14][15][16][17][18][19][20] In 1 case, a patient with congestive heart failure and supraventricular tachyarrythmia developed thyroid storm following administration of amiodarone, failed standard therapy for thyroid storm, and subsequently received TPE with an initial improvement in clinical state. However, the improvement was not sustained and the patient passed away from cardiac failure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in preoperative and post-operative management of severely hyperthyroid patients with contraindications to antithyroid drugs (13). It has also been used for the management of TS, predominantly in patients with Graves' disease with ophthalmopathy (14,15) or agranulocytosis (16,17) and in selected patients with toxic multinodular goiter (18). In a recent case of TS, plasmapheresis was done post surgery, where sleeve pneumonectomy was the precipitating event and the patient had not responded to standard antithyroid treatment (19).…”
Section: Discussionmentioning
confidence: 99%